2017
DOI: 10.1001/jamaophthalmol.2017.3431
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and Reproducibility of Superficial Macular Retinal Vessel Density Measurements Using Optical Coherence Tomography Angiography En Face Images

Abstract: IMPORTANCEThe repeatability and reproducibility of quantitative metrics from optical coherence tomographic angiography (OCTA) must be assessed before these data can be confidently interpreted in clinical research and practice.OBJECTIVE To evaluate the repeatability and reproducibility of OCTA-derived retinal vascular quantitative metrics. DESIGN, SETTING AND PARTICIPANTSIn this cross-sectional study, 21 healthy volunteers (42 eyes) and 22 patients with retinal disease (22 eyes), including 14 with age-related m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
175
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(192 citation statements)
references
References 17 publications
14
175
1
2
Order By: Relevance
“…14 Lei et al reported that the difference in signal strength between scans was positively correlated with the difference in VD and PD measurements and also reported that if the signal strength increased by one unit, the VD increased by 1.4 mm -1 when the signal strength was at least 7. 10 Similarly, we found a statistically significant correlation between signal strength and the mean VD (B, 1.16; p<0.001), and the signal strength and repeatability of the VD were also significantly correlated using univariate regression (table 3). Although they did not show a statistically significant result in multivariate regression, the signal strength and VD seem to have a tendency towards a positive correlation.…”
Section: Figuresupporting
confidence: 63%
See 2 more Smart Citations
“…14 Lei et al reported that the difference in signal strength between scans was positively correlated with the difference in VD and PD measurements and also reported that if the signal strength increased by one unit, the VD increased by 1.4 mm -1 when the signal strength was at least 7. 10 Similarly, we found a statistically significant correlation between signal strength and the mean VD (B, 1.16; p<0.001), and the signal strength and repeatability of the VD were also significantly correlated using univariate regression (table 3). Although they did not show a statistically significant result in multivariate regression, the signal strength and VD seem to have a tendency towards a positive correlation.…”
Section: Figuresupporting
confidence: 63%
“…3 OCTA also provides quantitative metrics about the retinal microvasculature, so it can help identify subclinical retinal vascular diseases and can assist in the diagnoses and follow-ups of many types of retinal diseases. 4 5 The Cirrus HD-OCT 5000 with AngioPlex software (Carl Zeiss Meditec, Dublin, California, USA; V. 10.0) automatically provides quantitative measurements of the vessel density (VD), perfusion density (PD) and foveal avascular zone (FAZ) area of the superficial capillary plexus. These metrics can be useful in clinical practice for patients with many types of retinal diseases, but establishing the repeatability of these measurements is critical for its use in clinical situation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that VD showed significantly lower values in EFI SS-OCTA than in SS-OCTA images acquired without EFI. This is not surprising as we have seen lower VD values in 6×6 mm field images compare to 3×3 mm field images in a prior study—this was thought to be due to differences in transverse resolution between difference scan patterns 17. One would expect EFI scans that cover a larger territory (with the same number of A-scans) would have an effective lower resolution, which would translate to a lower VD.…”
Section: Discussionsupporting
confidence: 48%
“…Previously, we observed lower VDs in 6×6 mm vs 3×3 mm spectral-domain OCTA images, likely because 6×6 mm scans cover a larger territory with the same number of A-scans, and thus have a lower effective resolution and lower VDs, than do 3×3 mm scans 18. Similarly, since 6×6 mm and 12×12 mm SS-OCTA images have lower resolutions than do 3×3 mm SS-OCTA images, they may also have a lower resolution with which to identify microvasculature damage.…”
Section: Discussionmentioning
confidence: 65%